2021
DOI: 10.12669/pjms.37.2.2787
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ketamine-midazolam combination and propofol-fentanyl combination on procedure comfort and recovery process in pediatric colonoscopy procedures

Abstract: Objective: To compare the efficacy and safety of midazolam-ketamine combination versus fentanyl-propofol combination in pediatric diagnostic colonoscopy. Methods: This is a retrospective study of 68 children undergoing diagnostic gastroenterology with midazolam-ketamine combination (Group-K) or with fentanyl-propofol combination (Group-P) in the pediatric gastroentology department at a Turkish tertiary hospital between January 2015 and June 2017. An intravenous midazolam was administered one minute befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…RSS varied more in group FP, while variations according to our results for group KP and group C were the same. Compared with a study using fentanyl-propofol and ketamine-midazolam sedation protocol in children, RSS was higher in group ketamine-midazolam,[ 18 ] on the basis of which we could conclude that combination of ketamine-propofol is better in relation to the already mentioned ones. In means of sedation-related complications, we observed that patients in Group KP were also less likely to suffer from complications such as desaturation, which was most common complication in Group FP.…”
Section: Discussioncontrasting
confidence: 56%
“…RSS varied more in group FP, while variations according to our results for group KP and group C were the same. Compared with a study using fentanyl-propofol and ketamine-midazolam sedation protocol in children, RSS was higher in group ketamine-midazolam,[ 18 ] on the basis of which we could conclude that combination of ketamine-propofol is better in relation to the already mentioned ones. In means of sedation-related complications, we observed that patients in Group KP were also less likely to suffer from complications such as desaturation, which was most common complication in Group FP.…”
Section: Discussioncontrasting
confidence: 56%
“…11 , 12 Therefore, timely interventions to promote recovery are particularly important. Ketamine has anti-inflammatory and neuroprotective proprieties, 13 , 14 with significant analgesic effects at low doses and narcotic effects at high doses. 15 Esketamine is twice as potent as racemic ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Pain during the colonoscopy occurs due the air distension maneuvers of the colon and traction of the mesocolon, which is why patients scheduled for lower digestive endoscopy request it to be performed under sedation or analgosedation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%